2019
DOI: 10.1016/j.eucr.2019.100920
|View full text |Cite
|
Sign up to set email alerts
|

Late results of bilateral scrotal flap

Abstract: We present you a late result of 27 year old man, who was operated in 2009 using bilateral scrotal flap (BSF) for paraffinoma localized to the penis, scrotum and pubic area. In 2010 the patient was operated again, because horseshoe relapse engaged the penis base, doing simple excision.Ten years later, the patient have excellence functional and cosmetic results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…The first and most used technique was the bilateral scrotal flap described in 11 studies and performed in 94 patients (61.8%) [ 4 , 18 , 21 , 23 , 24 , 26 , 27 , 28 , 32 , 33 ] Thirty-five out of 94 underwent a concomitant scrotoplasty [ 23 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…The first and most used technique was the bilateral scrotal flap described in 11 studies and performed in 94 patients (61.8%) [ 4 , 18 , 21 , 23 , 24 , 26 , 27 , 28 , 32 , 33 ] Thirty-five out of 94 underwent a concomitant scrotoplasty [ 23 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…4,13,21 One-stage penile skin reconstruction can be performed using a bilateral scrotal flap, which is a simple and effective method to treat SLP. 20,22,23 However, wound dehiscence or skin necrosis occurs frequently at the distal part of the flap, particularly near the ventral and dorsal subcoronal T-style anastomosis due to the poor blood supply in this area. 6 In their study, Shin et al found delayed wound healing and wound infection in all patients who underwent T-style anastomosis.…”
Section: Discussionmentioning
confidence: 99%
“…The study population in related articles is low, and the majority of publications are case reports or case series. 18,22,24 In clinical trials with relatively larger case numbers, patients in different stages of SLP were operated on following different reconstruction techniques. 1,13,14,16 SLP has no widely accepted classification system regarding the severity and extension of skin defects.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 paraffin or exogenous oil remains stable and semi-solid at room temperature but melts when it is warm. 3,4 The lack of enzymes in the human body to degrade paraffin causes various complications. Most of them, in the form of deformities, are the result of a granulomatous reaction.…”
Section: Introductionmentioning
confidence: 99%